Comparing humoral immune response in adult measles patients and measles vaccinated subjects - A. P. Toptygina (Sankt-Peterburg : NIIÈM imeni Pastera, 2021)
Introduction. The implementation of the WHO Measles Elimination Program has yielded serious results, but in recent years an increase in the incidence rate of this infection has been observed. In particular, according to the WHO, in 2019 vs. 2018 measles morbidity was elevated by 3-fold worldwide. While investigating measles outbreaks among patients, apart from unvaccinated subjects, a substantial group of adults vaccinated in childhood was distinguished. The aim of this work was to examine the characteristics of humoral measles immunity in adult measles patients as well as subjects after measles vaccination. Materials and methods. 50 adult measles patients aged 20 to 55 years were examined. In all patients, the diagnosis was confirmed clinically and by laboratory assays by detecting measles IgM antibodies. The second group consisted of 50 conditionally healthy seronegative age-matched adults, vaccinated with the live measles vaccine (Microgen, Russia). Peripheral blood samples were collected from the cubital vein in total volume of 4 ml on 6±1 day after the onset of rash in patients as well as 6 weeks after vaccination. Specific measles antibodies and their avidity were determined by ELISA using the commercial Avidity: Anti-Measles Viruses ELISA/IgG kit (Euroimmun, Germany). Results. It was shown that people aged 20—35 years more likely suffered from measles than elderly. And it was in this age group that healthy measles seronegative individuals were more abundant. Among vaccinees, 44% responded to vaccination with the primary type of immune response, and 56% responded with the secondary type, while among measles patients, 34% and 66% responded with the primary and secondary type, respectively, as follows from the spectrum of specific IgG subclasses and the antibody avidity assay. The secondary type of immune response indicates that these subjects were apparently vaccinated against measles in childhood, but lost with time long-lived plasma cells producing protective antibodies. While comparing the parameters of specific humoral immunity in groups with acute measles infection (day 6 from the onset of rash) and early convalescents (3 weeks after the onset of rash), it was shown that the level of specific IgG increased threefold in early convalescents (p < 0.01) compared with those at acute phase. The level of specific IgA, on the contrary, decreased from 73.44 (69—75.3) Me/ml to 48.64 (45—56.4) Me/ml, but remained very high. At the same time, the spectrum of specific IgG subclasses shifted from primary immune response (high IgG3 and low IgG1) to secondary response (low IgG3 and high IgG1), which is typical for the response of emerging memory B cells.